2012
DOI: 10.1111/j.1365-263x.2011.01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary levels of Bifidobacteria in caries‐free and caries‐active children

Abstract: Salivary levels of Bifidobacteria are significantly associated with caries experience in children. The salivary levels of this genus may be a useful marker of caries risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
5
32
0
Order By: Relevance
“…The probably most cariogenic Bifidobacterium frequently discussed is B. dentium, but we know little about the factors that influence its colonization of the dentition. Its numbers are under the detection limit (as in our study) or very low on caries-free tooth surfaces, but high in deep lesions [13], and data from studies of denture plaque provide further insight into its ecology [25,26]. Unlike mutans streptococci, B. dentium does not colonize hard surfaces per se since denture plaque associated with denture stomatitis harbored high levels of mutans streptococci, lactobacilli and yeasts but not B. dentium [13].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The probably most cariogenic Bifidobacterium frequently discussed is B. dentium, but we know little about the factors that influence its colonization of the dentition. Its numbers are under the detection limit (as in our study) or very low on caries-free tooth surfaces, but high in deep lesions [13], and data from studies of denture plaque provide further insight into its ecology [25,26]. Unlike mutans streptococci, B. dentium does not colonize hard surfaces per se since denture plaque associated with denture stomatitis harbored high levels of mutans streptococci, lactobacilli and yeasts but not B. dentium [13].…”
Section: Discussionmentioning
confidence: 80%
“…Additional species have been associated with disease when S. mutans or lactobacilli were absent, including Bifidobacterium dentium [6,13,22], and more recently Scardovia wiggsiae [11,23,24]. The probably most cariogenic Bifidobacterium frequently discussed is B. dentium, but we know little about the factors that influence its colonization of the dentition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…wiggsiae, which is a member of Bifidobacteriaceae family, is recently identified and thought to be an important part of cariesrelated microbial complex [9]. Studies have showed that there is a relationship between the presence of caries and Bifidobacteriaceae Bifidobacteria and Scardovia's high prevalence [7,8,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Kanasi et al reported that S. mutans and Bifidobacterium species are in a strong relationship with S-ECC [7]. Kaur et al found that high levels of salivary bifidobacteria are also associated with the increased number of caries activity in children [8]. Tanner et al identified a highly significant relationship between the S-ECC and S. mutans, Scardovia wiggsiae, Veillonella parvula, Streptococcus cristatus, Fusobacterium nucleatum and Actinomyces gerencseriae Materials and Methods [9].…”
mentioning
confidence: 99%